The Role of Innovation Capability in MSME Sustainability During the Covid-19 Pandemic - Yunita Sari; Yetty Oktarina; Munajat; Mardiah Kenamon (International Journal of Social Science and Business, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are business activities capable of expanding employment and providing the economic services for society widely, and also play roles in equalizing and increasing people's income, encouraging economic growth, and realizing national stability. Micro, Small and Medium Enterprises (MSMEs) also play an essential role in improving the community's economy at the city and regency levels. This study aims to analyze the empirical evidence that the capabilities and environmental factors carried out by MSMEs have a positive effect on innovation, both product innovation and process innovation. The method used in this study is the Structural Equation Model PLS analysis. The population in this study is the total number of MSMEs which registered with the Department of Trade and Industry in 2020 as many as 31591 businesses. The data collection technique is done by distributing questionnaires. Measurement models are assessed by testing the reliability of each item, converging validity and discriminant validity. The results of the analysis show empirical evidence that innovation capability and environmental factors carried out by the MSME sector have a significant positive effect on innovation, both product innovation and process innovation. This study concludes that innovation capability and environmental factors in the MSME sector can increase innovation and have an impact on the sustainability of MSMEs. The contribution of this research is that the capability of innovation and environmental factors can increase the innovation made by MSMEs.